If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(a-3)+3(a+5)=4(2a-1)-5
We simplify the equation to the form, which is simple to understand
2(a-3)+3(a+5)=4(2a-1)-5
Reorder the terms in parentheses
+(+2a-6)+3*(a+5)=4*(2a-1)-5
Remove unnecessary parentheses
+2a-6+3+*(+a+5+)=+4+*(+2a-1+)-5
Reorder the terms in parentheses
+2a-6+(+3a+15)=4*(2a-1)-5
Remove unnecessary parentheses
+2a-6+3a+15=+4+*(+2a-1+)-5
Reorder the terms in parentheses
+2a-6+3a+15=+(+8a-4)-5
Remove unnecessary parentheses
+2a-6+3a+15=+8a-4-5
We move all terms containing a to the left and all other terms to the right.
+2a+3a-8a=-4-5+6-15
We simplify left and right side of the equation.
-3a=-18
We divide both sides of the equation by -3 to get a.
a=6
| -5x-7x=32 | | 3y-9=-18+3 | | 2p/6+25=37 | | 3y-9=-12 | | 9x+8=9x+72 | | 14x+5=10x+7 | | -a-4=3a | | 21-7y=6(4y+3) | | 8-6d=12 | | 3y-9=-6+3 | | 7xn=3-5xn | | 8.4x+0.3(x-4)= | | 4.5(4*-12)=144 | | 3y-9=18+3 | | -35=-5+9(s+3) | | 6e+5(w-2)=23 | | 5w-3=-18 | | 3y-9=12+3 | | 2+3(x+1)=21 | | 18x+18=162 | | 6x+x^2=-9 | | -2(3)+8= | | -4x=-2(x+3) | | a^6+125b^3=0 | | 6x=5x-26 | | px+2p=2 | | -2(x+9)+3(2x-3)=-32 | | 9t-10=6t | | x^2(x^2-5)-2x(x^2-4)+4=0 | | 6x^4-8x^3+10x= | | 3y-9=6+3 | | (3*-2*1)+2= |